MORPHOLOGICAL AND BIOCHEMICAL DIFFERENCES OF TREES WITH DIFFERENT RESISTANCE TO ANNOSUM ROOT ROT - Dyshko, V. A.; Ustskyy, I. M.; Mykhaylichenko, O. A. (Forestry and Forest Melioration, 2018)
Introduction Effective organization of the selection process for the creation of productive and sustainable plantations is becoming increasingly important. Traditional methods based on group and individual selection do not allow fully consideration of the properties of young plants resistance to pathogens, so a significant part of artificial plantations is often affected by insect pests and disease. For the Scots pine which is principal forest forming species in Ukraine, the most dangerous pathogen is annosum root rot (Heterobasidion annosum (Fr.) Bref., 1889), which affects most conifer species, leading to a gradual weakening and dying of trees in plantations. The aim of the study was to determine differences in the stability of trees in pine populations affected by annosum root rot. Materials and Methods Three tree condition categories were selected for study: “Resistant” - trees without external disease symptoms, located in the root rot foci area; “Diseased” - trees with strong indication of disease, located on the gap margins; “Healthy” – located in the inter-foci area. For all the selected trees, the taxation indices are measured (height, diameter) and samples of phloem are collected for the determination of biochemical compounds (proteins, proanthocyanidines, catechines). Results and Conclusions It was found that “Resistant” trees are characterized by somewhat lower height than trees of other categories of health status. Relation between the diameters of trees and sanitary conditions was not found. The content of the studied primary and secondary metabolism compounds in trees that are in the foci is higher than that in the trees between the focal areas. It was found that pathogen impact causes the imbalance between the synthesis of primary and secondary metabolites in phloem that in turn affects the physiological state of trees. The degree of parameters variability in groups of trees in affected area is considerably higher than in healthy trees without pathogen impact. The lowest variability of these parameters is in the group of "healthy" trees. The weak correlation between the main taxation indices and content of biochemical compounds in phloem is found. The functional relationships between the main growth characteristics and biochemical compounds are very complex and do not directly claim causation, but only tendencies to it.